Tahlil al-Akhtha' fi Maharah al-Kitabah Lada Thullab fi Jami'ah al-Islamiyah al-Hukumiyah Mandailing Natal: Dirasah al-Lughawiyah al-Bainiyah Litahsin Ta'lim al-Lughah al-'Arabiyah - Ahmad Nurul Huda (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2025)
This study examines linguistic errors in Arabic writing skills among students of the Arabic Language Department at STAIN Mandailing Natal, Indonesia. The study aims to identify the types of common writing errors and their underlying causes by employing Interlanguage Theory and Error Analysis as its theoretical framework, with the objective of contributing to the improvement of Arabic language instruction. The findings reveal that students experience various errors in spelling, morphology, syntax, and sentence structure, with a noticeable influence of their first language (Indonesian) on their written production. These errors reflect systematic patterns rather than random mistakes, indicating incomplete mastery of Arabic linguistic rules. The study recommends the implementation of innovative pedagogical approaches, including contrastive analysis, reinforcement of grammatical competence, and contextualized writing practice, to enhance students’ Arabic writing proficiency.